2017
DOI: 10.1155/2017/8426348
|View full text |Cite
|
Sign up to set email alerts
|

Design of LPV-Based Sliding Mode Controller with Finite Time Convergence for a Morphing Aircraft

Abstract: This paper proposes a finite time convergence sliding mode control (FSMC) strategy based on linear parameter-varying (LPV) methodology for the stability control of a morphing aircraft subject to parameter uncertainties and external disturbances. Based on the Kane method, a longitudinal dynamic model of the morphing aircraft is built. Furthermore, the linearized LPV model of the aircraft in the wing transition process is obtained, whose scheduling parameters are wing sweep angle and wingspan. The FSMC scheme is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…A flight mechanics modeling method is proposed to solve the time-varying characteristics of the aerodynamic parameters, moment of inertia and centroid of a variant aircraft during the variant process, and flight simulation verification is carried out with the ''gull wing'' aircraft [6]. The Kane multibody modeling method is used to establish a nonlinear dynamic model including the variant structure of the morphing aircraft [7], [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A flight mechanics modeling method is proposed to solve the time-varying characteristics of the aerodynamic parameters, moment of inertia and centroid of a variant aircraft during the variant process, and flight simulation verification is carried out with the ''gull wing'' aircraft [6]. The Kane multibody modeling method is used to establish a nonlinear dynamic model including the variant structure of the morphing aircraft [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is impossible to accurately express the dynamic characteristics of a morphing aircraft in which a plurality of deformation parameters exist. At the same time, the above literature does not consider the existence of model perturbation and interference, and later studies have shown that the H ∞ -type controller has a poor control effect under this condition [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the problem of morphing aircraft flight controller design has been addressed via various approaches that can capture the parameter-varying nature of the system, such as linear parameter-varying control, 1217 adaptive control, 1822 and sliding mode control. 16,17 However, no previous study has considered handling qualities criteria. The objective of this study is to develop a control system that can fully exploit the shape-changing ability while rigorously satisfying all the handling qualities requirements at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a gain scheduling (conventional and linear-parameter varying) approach, model-reference adaptive control scheme, and various nonlinear control techniques such as feedback linearization, sliding mode, and back-stepping control methods have been studied. Consequently, the problem of morphing aircraft flight controller design has been addressed via various approaches that can capture the parameter-varying nature of the system, such as linear parameter-varying control, [12][13][14][15][16][17] adaptive control, [18][19][20][21][22] and sliding mode control. 16,17 However, no previous study has considered handling qualities criteria.…”
Section: Introductionmentioning
confidence: 99%